Posterior Reversible Encephalopathy Syndrome: An Unusual Complication of Benzodiazepine Poisoning: A Case Report - Punia, Vedpal Singh; Mittal, Shaavi; Shetty, Apoorva; Bansal, Naman; Garg, Prashant; Kumar, Prem; Pratap, Neelabh (International Journal of Medical Toxicology and Forensic Medicine, 2022)
Posterior Reversible Encephalopathy Syndrome (PRES), also known as Reversible Posterior Leukoencephalopathy Syndrome, presents with rapid onset symptoms, including headache, seizures, altered consciousness, and visual disturbance. It is seen most frequently in settings of acute hypertension and is usually related to eclampsia. Only a few cases in the literature described PRES syndrome following benzodiazepines. We present a young male with benzodiazepine poisoning brought to the hospital in a deep coma, hypoxia, acidosis, and shock. Diagnosis of PRES was made on history, clinical examination, and radiologic findings of symmetric bilateral hyperintensities on T2 weighted Magnetic Resonance Imaging (MRIs) representing vasogenic edema.